Effect of replacing fishmeal with 70 cottonseed protein concentrate on growth performance, liver health, muscle texture, intestinal microbiome, and wastewater parameters in hybrid grouper (Epinephelus fuscoguttatus♀ × E. lanceolatus♂) juvenile - Kangze Xv; Adinda Luthfiah; Min Xue; Hao Wang; Tingting Wang; Xin Zhang; Dengbao Fan; Beiping Tan; Wei Zhang (Aquaculture Reports)
As a superior protein historically applied in aquaculture, cottonseed protein has been processed by various deep processing methods to improve its utilization in aquafeeds. In this study, 70 cottonseed protein concentrate with low-gossypol (70 C) was used to replace fishmeal (20 %, 40 %, 60 %, and 80 %) to evaluate the effect on hybrid grouper (Epinephelus fuscoguttatus♀ × E. lanceolatus♂) juveniles (15.00 ± 0.05 g). After a 7-week feeding trial, 40 % 70 C replacing fishmeal had no negative impact on the growth performance of juveniles (P > 0.05). Serum biochemical indices, including alanine aminotransferase (ALT), albumin (ALB), and total cholesterol (TC), were significantly reduced with an increase in dietary 70 C (P < 0.05), suggesting that liver function was impaired, which was further confirmed by the alteration of hepatic morphology. Moreover, the core microbiota of the intestine were majorly Proteobacteria, Firmicutes, Cyanobacteria, Bacteroidota, and Actinobacteriota, etc. at the Phylum level. At the Genus level, Enterobacter significantly decreased with increasing dietary 70 C (P < 0.05). NS3a_marine_group, Sphingomonas Amaricoccus, Craurococcus_Caldovatus, and Agrococcus achieved the highest abundance, whereas Nocardioides and Lachnoclostridium had the lowest abundance in the 70 C20 group. Furthermore, the abundance of Photobacterium and Amaricoccus was more overrepresented in the 70 C60 group than in the other two groups (P < 0.05). The abundance of the predicted pathways related to butanoate metabolism increased in the 70 C group compared to the FM group. Thus, we hypothesized that dietary 70 C would influence the composition of the intestinal microbiota, thereby affecting flesh texture and degrading water quality. Our research provides a theoretical basis for widening the application of cotton protein concentrates in grouper aquafeeds.